Declining incidence of pyloric stenosis in New Zealand. Issue 10 (26th August 2019) - Yau, Annie; Cha, Ryan; Jayaratnam, Sridharan; Wilson, Toni; Kukkady, Askar; Evans, Stephen M.; Wells, Jonathan M.
Abstract : Background: Pyloric stenosis is a relatively common paediatric surgical condition, but a worldwide decline in its incidence has been observed in recent decades. The objective of this study was to identify if the incidence of pyloric stenosis in New Zealand has been declining. Methods: A retrospective review of the four New Zealand paediatric surgical centres' theatre databases from 2007 to 2017. Demographic data were recorded for all infants who had a pyloromyotomy and annual incidences of pyloric stenosis calculated. Results: A total of 393 infants underwent a pyloromyotomy for pyloric stenosis during the study period. Most infants (81%) were of European ethnicity. There was a significant decline ( P = 0.0001) in the national incidence of pyloric stenosis from 0.73/1000 live births (LB) in 2007 to 0.39/1000 LB in 2017. From 2007 to 2017, the incidence of male infants with pyloric stenosis declined from 1.27/1000 LB to 0.62/1000 LB. The current annual incidence of pyloric stenosis in New Zealand is 0.39/1000 LB. Conclusions: The incidence of pyloric stenosis in New Zealand has significantly declined in the last decade and is currently the lowest reported incidence in the world involving a predominantly European cohort. A decline in male infants developing pyloric stenosis was also observed. Further study is required to investigate causes for this low incidence and declining trend.